Сущность типологии государства - Муренко, Елена Леонидовна (НТУ "ХПИ", 2014)
В данной научной статье освещаются вопросы типологии государства. В результате анализа научной литературы определено значение «государства» и его типы – формационный и цивилизационный, проведена классификация типологии государства по различным признакам. Статья раскрывает и подчеркивает важность дальнейшего изучения данного вопроса, так как от степени познания указанной темы зависит эффективность функционирования городов, регионов, областей и всего государства.

This scientific article highlights the questions of typology of the state. The world today is comprised of many types of states. The contemporary security environment features many more state actors than it did a century ago. Not only are there more states, but there are also many more types of states, many of which can be classified. An analysis of the scientific literature value defined "state" and its types - formation and civilization, the classification of the typology of the state on various grounds. Governments can be classified into several types. The author considers some of the more common types of governments in this paper. The article reveals and emphasizes the importance of further study of this issue because the degree of cognition the specified theme depends on efficiency of functioning of cities, regions, provinces and the entire state.
The essence of the typology of state
Keywords: типология государства; цивилизация; форма правления; монархия; республика; state; typology of state; civilization; form of government; monarchy; republic